2009
DOI: 10.1164/rccm.200807-1097oc
|View full text |Cite
|
Sign up to set email alerts
|

Rapid DNA Methylation Changes after Exposure to Traffic Particles

Abstract: Rationale: Exposure to particulate air pollution has been related to increased hospitalization and death, particularly from cardiovascular disease. Lower blood DNA methylation content is found in processes related to cardiovascular outcomes, such as oxidative stress, aging, and atherosclerosis. Objectives: We evaluated whether particulate pollution modifies DNA methylation in heavily methylated sequences with high representation throughout the human genome. Methods: We measured DNA methylation of long interspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
454
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 595 publications
(487 citation statements)
references
References 41 publications
28
454
2
3
Order By: Relevance
“…6 Baccarelli et al 41 found decreased LINE-1 methylation in association with 7-day moving average black carbon and PM 2.5 levels, whereas no association was observed for Alu methylation. A controlled human exposure experiment observed hypomethylation of Alu and the toll-like receptor 4 (TLR4) gene among 15 healthy adults exposed to fine concentrated ambient particles (CAPs) for 130 min.…”
Section: Discussionmentioning
confidence: 99%
“…6 Baccarelli et al 41 found decreased LINE-1 methylation in association with 7-day moving average black carbon and PM 2.5 levels, whereas no association was observed for Alu methylation. A controlled human exposure experiment observed hypomethylation of Alu and the toll-like receptor 4 (TLR4) gene among 15 healthy adults exposed to fine concentrated ambient particles (CAPs) for 130 min.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, particulate air pollution has been associated with increased cardiovascular events, and lower blood DNA methylation has been found in processes related to cardiovascular morbidity . Lower blood DNA methylation has been also found after exposure to traffic particles (Baccarelli et al, 2009) and after prolonged exposure to black carbon and SO 4 particles (Madrigano et al, 2011). Other toxics associated with carcinogenesis, including asbestos, alcohol, radiation and arsenic, are known to act also by epigenetic mechanisms (Christensen and Marsit, 2011).…”
Section: Endocrine Disruptors and Toxicsmentioning
confidence: 98%
“…CGIs were considered to be hypermethylated if the Alexa647/Alexa555 ratio was >3, corresponding to log 2 r/g >1. 6. Intermediate values were considered as partial hypo-or hypermethylation (Fig.…”
Section: Cgi Methylation Status In Cas Andmentioning
confidence: 99%
“…Furthermore, human and animal studies consistently indicate that global DNA hypomethylation accompanies advanced atherosclerosis (3,4). Importantly, 2 recent human studies have indicated that circulating levels of inflammation markers and exposure to environmental risk factors for atherosclerosis were associated with hypomethylation of highly repeated elements of leukocyte DNA (5,6). Identifying the sequences undergoing demethylation in atherosclerosis could provide important insights into the molecular mechanisms of atherogenesis and possibly of diet-or environment-gene interactions (7).…”
Section: Introductionmentioning
confidence: 99%